Родство: стихи / Владимир Емельянов - Емельянов Владимир Иванович (Первая книга в столице, 1984)
Экземпляры: КР (20020330) / Инвентарный номер: у32944 / Сис.шифр: Р2 / Авт.знак: Е 60 / ГРНТИ: 17.82 / ББК: 84(2)